The meningococcus tamed? - Pollard, A; Moxon, E (2002)
Serogroup B Neisseria meningitidis is a frequent cause of invasive meningococcal disease, yet there are no effective vaccines suitable for routine immunisation. Limited efficacy has been shown with meningococcal outer membrane vacccines in children 4 years and older. Here we review the status of current research and consider new approaches to development of meningococcal serogroup B vaccines.